541.183 Kimyo va kimyoviy texnologiyalar: Physico-chemical properties of activated adsorbents based on Logan bentonite - Nazokat, G'aniyeva; Ochilov, Golibjon; Boymatov, Ismoiljon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article clarifies the physicochemical properties of adsorbents activated from Logon bentonite under various thermal and chemical conditions. It has been established that the desorption lines in the LBK and LBI intersect with the adsorption lines at a relative pressure R/Rs = 0.1–0.2, forming an adsorption hysteresis surface.